ANALISIS PENGARUH FAKTOR PRODUK PINJAMAN, PROSEDUR KREDIT DAN SUKU BUNGA KREDIT TERHADAP KEPUASAN ANGGOTA PADA KOPERASI SIMPAN PINJAM SWA MITRA DI DEMAK - Dewi Sri Handayani; Theresia Susetyarsi (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract Currently the development of cooperatives is quite good. Many cooperatives are established both in the city center and in the regions. The existence of this cooperative is very helpful for its members or prospective members in fulfilling their daily needs. Cooperatives as one of the business entities that carry out activities based on cooperative principles as well as driving the people's economy based on the principle of kinship. The purpose of this study is to determine and analyze the effect of Loan Products, Credit Procedures and Credit Interest Rates on the Satisfaction of Swa Mitra Cooperative Members in Demak. The research population is the active members of the cooperative, amounting to 564 and the specified sample is 85 people. The analytical tool used is multiple linear regression with the help of SPSS. The results of the study indicate that Loan Products, Credit Procedures and Credit Interest Rates have a positive and significant influence. This is indicated by the positive value of the regression coefficient, t count which is greater than t table and the significant value for loan products, credit procedures and credit interest rates is less than 0.05. As a suggestion, one should be careful not to go too far from the interest rate set by Bank Indonesia, considering that interest rates have a major influence on the satisfaction of cooperative members.